Contact angle and surface tension of water on a hexagonal boron nitride monolayer: a methodological investigation. Issue 4 (24th March 2019) - Essafri, Ilham; Le breton, Jean-Christophe; Saint-Jalmes, Arnaud; Soldera, Armand; Szymczyk, Anthony; Malfreyt, Patrice; Ghoufi, Aziz
ABSTRACT: Recently, many works have been focused on the wetting properties of water on hexagonal boron nitride (hBN) monolayers given their potential application as reverse osmosis membrane in desalination processes. Among interfacial properties contact angle and surface tension are probably the most studied. In this work, we investigated the computational procedures such as electrostatics interactions calculation, the cutoff and the force field effects on the modelling of water nanodroplet on hBN monolayer to provide the cheapest route in terms of computational time. Surface tension of solid–liquid (γ SL ) and solid–vapour (γ SV ) interfaces, the Young's contact angle and the line tension were also managed by combining the direct calculation and the Young–Dupré equation. For the first timeγ SV was evaluated whereas a negative line tension of order of magnitude of 10 −15  N was calculated in fair agreement with the theoretical works.